CURRICULUM COMPACTING: DIFFERENTIATING ALGEBRA SYLLABUS ACCORDING TO THE READINESS LEVELS OF GIFTED STUDENTS - Joli, Nurul Suzaina; Kamarulzaman, Mohd Hasrul; Ishak, Noriah Mohd; Hissam, Fairuz Adlidna; Azhari, Azrina Md; Hazir, Nursakinah Mat (PEOPLE: International Journal of Social Sciences, 2022)
Gifted learners are unique, in the way they learn i.e. in processing new information and knowledge. Because of their uniqueness, teachers need to identify their learning preferences prior to lesson planning, and differentiate their instruction accordingly with appropriate classroom strategies. This study investigated a differentiation strategy called curriculum compacting, which was applied in the teaching of Algebra among gifted students. Curriculum compacting allows learners who have the potential to pursue higher level or more advanced topics at faster rate. Of the national standard, Algebra I, II, and III are introduced to Form 1, Form 2, and Form 3 respectively. However, at Kolej PERMATApintar, Algebra I, II, and III were compacted, in accordance with the gifted students’ learning preferences i.e. readiness levels, and taught to Form 1 gifted students. A total of 166 Form 1 gifted students participated in this experimental study. Test results were gathered and analyzed representing the effect of curriculum compacting on the gifted students’ achievement. The findings revealed that 38.6% students had excellent understanding of the compacted Algebra syllabus (marks between 85-100), 44% achieved good understanding (marks between 65-84), 11.4% had moderate understanding (marks between 50-64), and only 6% had poor understanding (marks between 0-49). From this study, we can conclude that curriculum compacting is a beneficial differentiation technique for gifted students in the teaching and learning of Algebra.